SCIENTIFIC PRODUCTION OF PATIENT NURSING CARE SPINAL CORD INJURY: A BIBLIOMETRIC ANALYSIS. - Pereira Melo de Albuquerque, Geyslane; Silva Coura, Alexsandro; Chaves Camilo Fernandes, Marta Regina; Sátiro Xavier de França, Inácia; Santos Baptista, Rosilene; Oliveira do Nascimento, Monique (Revista de Pesquisa: Cuidado é Fundamental)
Objective: To describe the distribution of scientific production of nursing care to patients with spinal cord trauma and to verify which themes are most addressed. Method: Bibliometric analysis through the Bradford Law, Zipf Law and textual statistics made with publications in Portuguese, English and Spanish, from 1978 to 2018. Results: Sample composed of 33 articles distributed in 13 journals, most of them original and of quantitative approach. Brazil has published the largest number of articles, presenting the third position of the journals in the Bradford nucleus. An average Bradford multiplier value (XmB) = 2.1 was identified. The terms with the highest semantics were: spinal cord injury, patient, nursing, nurse and care. Conclusion: The bibliometric indicators showed a scientific production with low productivity, but with a tendency to growth in the last decades. Further studies on the subject are needed to improve the care offered to patients with spinal cord injury.